Platformy streamingowe i ich wpływ na lokalny rynek audiowizualny - Morozow, Iwona (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
The article focuses on outlining the potential direction of research on the Polish audiovisual market in the face of its platformization. The aim is to analyze and problematize the contexts of cooperation between an independent, local production company and a global platform in the film production process. It is an attempt to capture the characteristics of this cooperation by juxtaposing general industry practices with work culture, standards and rules specific to selected platforms and the long-term effect in the form of a potential impact on the diversification of production and its content. The outlined issues will be analyzed on the basis of industrial reflexivity based on cooperation with Netflix and HBO Max, collected using the method of partially structured in-depth interviews.